PELAKSANAAN EKSEKUSI TERHADAP BARANG JAMINAN YANG TIDAK MEMILIKI AKTA FIDUSIA BERDASARKAN PUTUSAN NO. REG. 81/Pdt.G/2018.PN.Pdg - Dora Tiara; Naldi Gantika (UNES Journal of Swara Justisia, 2020)
Financial institutions and banks provide financing for consumers, leasing, factoring. They generally use the procedure of the agreement which includes a fiduciary guarantee for fiduciary security objects. In practice, financial institutions provide movable goods requested by consumers. Consequently the debtor surrenders to the creditor in a fiduciary manner. Implementation of the executorial title by PT. Mandiri Tunas Finance is not through a court decision or fiduciary guarantee certificate, but only based on a power of attorney and agreement made by the collector . The sale of fiduciary collateral objects carried out by PT. Mandiri Tunas Finance does not go through public auctions but through separate sales; and Underhanded sales are not based on the agreement of both parties, the agreement is only based on PT. Mandiri Tunas Finance so that it harms the consumer. Actions taken by PT. Mandiri Tunas Finance does not provide legal certainty to both parties. The act of execution was carried out solely to safeguard assets regardless of legal certainty of the rights of consumers / debtors contained in fiduciary security objects in the form of car vehicles. Legal constraints of not registering the agreement are that execution cannot be carried out, based on Article 3 of the Minister of Finance Regulation No. 130 / PMK.010 / 2012 stating that finance companies are prohibited from withdrawing fiduciary objects in the form of motorized vehicles if the Fiduciary Registration Office has not issued a guarantee certificate fiduciary and hand it over to the finance company. With these provisions, PT. Mandiri Tunas Finance cannot execute if it does not register fiduciary collateral objects because without the registration of fiduciary collateral objects the fiduciary guarantee certificate cannot be issued.